2009
DOI: 10.1128/aem.00928-09
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Total Inflammatory Potential of Bioaerosols by Using a Granulocyte Assay

Abstract: Occupational health symptoms related to bioaerosol exposure have been observed in a variety of working environments. Bioaerosols contain microorganisms and microbial components. The aim of this study was to estimate the total inflammatory potential (TIP) of bioaerosols using an in vitro assay based on granulocyte-like cells. A total of 129 bioaerosol samples were collected in the breathing zone of workers during their daily working routine at 22 biofuel plants. The samples were analyzed by traditional assays f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
43
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 28 publications
2
43
1
Order By: Relevance
“…The assay is based on the differentiated HL-60 cell line, which, upon exposure to microbial compounds, reacts by producing reactive oxygen species (ROS) quantifiable by a luminal-dependent chemiluminometric assay. In this study, measurement of TIP was conducted as described previously (55). Prior to analysis, all samples were subjected to ultrafiltration for removal of Tween, as Tween inhibits the cellular ROS response in the granulocyte assay.…”
Section: Selection Of Homesmentioning
confidence: 99%
See 2 more Smart Citations
“…The assay is based on the differentiated HL-60 cell line, which, upon exposure to microbial compounds, reacts by producing reactive oxygen species (ROS) quantifiable by a luminal-dependent chemiluminometric assay. In this study, measurement of TIP was conducted as described previously (55). Prior to analysis, all samples were subjected to ultrafiltration for removal of Tween, as Tween inhibits the cellular ROS response in the granulocyte assay.…”
Section: Selection Of Homesmentioning
confidence: 99%
“…Prior to analysis, all samples were subjected to ultrafiltration for removal of Tween, as Tween inhibits the cellular ROS response in the granulocyte assay. Ultrafiltration was also conducted as described previously (55). The chemiluminescence reaction caused by sample activity was measured with a thermostated (37°C) Orion II Microplate luminometer (Berthold Detection Systems, Germany), which measured relative light units (RLU) per second for 1 s every 120 s for 180 min.…”
Section: Selection Of Homesmentioning
confidence: 99%
See 1 more Smart Citation
“…92 Mechanistic studies have confirmed the presence of microbial components on PM samples and their ability to produce TLR-mediated signaling. 93 These studies demonstrate significant enhancement of the biological response to inactive PM with the addition of low levels of bacterial contamination.…”
mentioning
confidence: 91%
“…Also particles from combustion of dried animal drugs are described to be highly oxidative (Mudway et al 2005). Occupational exposure to bioaerosol components and the inflammatory potential of these bioaerosols are different in different working areas at the plants (Madsen 2006;Timm et al 2009). Furthermore the microbial dustiness of different biofuels (straw, wood chips, wood pellets and wood briquettes) differs (Madsen et al 2004) and also depends on the storage method and period (Sebastian et al 2006).…”
mentioning
confidence: 99%